2013
DOI: 10.5861/ijrsp.2013.250
|View full text |Cite
|
Sign up to set email alerts
|

Personality differences of college students with public and private Facebook profile: A big five model viewpoint

Abstract: Social networking sites are prevalent media in communication and self-expression among people across different ages. The study determined possible personality differences of Facebook users with public and private profiles and examined personality traits that are predictive of Facebook profile preference through a descriptive-predictive research design. Two hundred seventy college students (n=270) whose ages range from 15 to 27 were recruited from a private collegiate institution in Manila City. Findings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similar to previous studies, Australian Facebook users tends to be more socially lonely than non-users. Lastly, a recent study mentioned that the different ways Facebook users set their profiles whether public or private relies on tendencies to exercise greater degree of self-control, order and regulation (N. D. Datu, Datu, & Rungduin, 2013). Hence, it is said that Facebook profile settings can be influenced by innate predispositions in the form of personality traits.…”
Section: International Journal Of Research Studies In Educationalmentioning
confidence: 99%
“…Similar to previous studies, Australian Facebook users tends to be more socially lonely than non-users. Lastly, a recent study mentioned that the different ways Facebook users set their profiles whether public or private relies on tendencies to exercise greater degree of self-control, order and regulation (N. D. Datu, Datu, & Rungduin, 2013). Hence, it is said that Facebook profile settings can be influenced by innate predispositions in the form of personality traits.…”
Section: International Journal Of Research Studies In Educationalmentioning
confidence: 99%
“…When mutual benefit turns into a conflict of interests in some cases, the parties have to develop a new strategy according to the behaviors of each other. Studies have shown that five factors have a significant influence on shaping behaviors of individuals in social networks (Eşkisu et al 2017;Ryan and Xenos 2011;Mahajan 2009;Tsai et al 2017;Datu et al 2013;Liu and Campbell 2017). Altıntaş (2017) in-depth interviews held with 10 people with the highest in order to find out how adults perceived violence news on Internet news sites.…”
Section: Introductionmentioning
confidence: 99%